2021
DOI: 10.1038/s41598-021-99794-9
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebrospinal fluid markers for synaptic function and Alzheimer type changes in late life depression

Abstract: To explore markers for synaptic function and Alzheimer disease (AD) pathology in late life depression (LLD), predementia AD and normal controls (NC). A cross-sectional study to compare cerebrospinal fluid (CSF) levels of neurogranin (Ng), Beta-site amyloid-precursor-protein cleaving enzyme1 (BACE1), Ng/BACE1 ratio and Amyloid-β 42/40 ratio, phosphorylated-tau and total-tau in LLD with (LLD AD) or without (LLD NoAD) AD pathology, predementia AD and normal controls (NC). We included 145 participants (NC = 41; pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…The multi-site DDI cohort study comprised at-risk and clinical cases with subjective cognitive decline (SCD) (Jessen et al, 2014 ) and MCI (Albert et al, 2011 ) who had standardized MRI and CSF measurements (Fladby et al, 2017 ; Siafarikas et al, 2021 ). In addition, healthy controls (HC) were included from spouses of patients and from patients who completed lumbar punctures in connection with orthopedic surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-site DDI cohort study comprised at-risk and clinical cases with subjective cognitive decline (SCD) (Jessen et al, 2014 ) and MCI (Albert et al, 2011 ) who had standardized MRI and CSF measurements (Fladby et al, 2017 ; Siafarikas et al, 2021 ). In addition, healthy controls (HC) were included from spouses of patients and from patients who completed lumbar punctures in connection with orthopedic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, we categorized patients with 18F-AV-45 values ≥1.11 into the Aβ+ group, while those with values below this threshold were assigned to the Aβ− group. In the DDI dataset, we established Aβ42/40 ratio cutoffs with a range of 0.077, derived from receiver operating curve (ROC) analysis using visual read results of Flutemetamol (18F-Flut) PET scans as the standard reference (Siafarikas et al, 2021 ). Aβ measurements were excluded from predictor variables in the model, as they were partially used for status definition in DDI and represent the same features as measured with PET in ADNI.…”
Section: Methodsmentioning
confidence: 99%
“…An optimum cut-off for Aβ 42/40 ratio at ≤0.077 was determined following receiver operating curve (ROC) analysis using visual read of [18F]-Flutemetamol PET scans as the standard of truth. 50 We selected three groups based on the A/T/N staging at baseline: (i) cases with amyloid pathology without tau pathology (A+/T−/N−, n = 86), (ii) cases with both amyloid pathology and tau pathology (A+/T+/N+, n = 90), and (iii) healthy controls with normal CSF Alzheimer’s disease biomarkers (A−/T−/N−, n = 74). Longitudinally collected CSF samples were available for subsets from all groups (A-/T-/N-: n = 33; A+/T-/N-: n = 39; A+/T+/N+: n = 28) at approximately 2-year intervals ranging between one and 6 years from baseline (see Supplementary Table 1 for details).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that cardiovascular diseases, metabolic disorders, endocrine disorders, anxiety and depression are all risk factors for the development of AD. Early intervention of related risk factors have been proved to have an effect on reducing the risk of AD, even reversing the cognitive loss of MCI patients and delaying the progress of the disease ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%